From Human Art to Artificial Intelligence and Back: Practical Considerations from Academia - Nataša Z. Janković; Aleksandar Đ. Vuletić (Inovacije u Nastavi)
Globalization has had an impact on us both as individuals and social actors, with technological advancements setting the course. Hybrid formats, which blend human-machine interaction with cooperative classroom methods, have become a regular feature of modern education. While artificial intelligence (AI) can, undoubtedly, add to both independent individual study and collaborative on-site practice, the question is to what extent it can be perceived rather as support or threat to human learning and activity. Relying on a mixed-methods approach, this paper investigates the cognitive-affective, pragmatic, and ethical aspects of using AI tools in art students’ learning of English for specific purposes (ESP), and the value they attribute to it in education, their personal lives, and especially in the world of art.